INCREASING ACTIVITIES AND RESULTS OF LEARNING OF 4TH CLASS SCHOOL STUDENTS THROUGH APPLICATION OF LEARNING MODEL BASED ON PROBLEM-BASED LEARNING PROBLEMS FOR THEMATIC LEARNING - Yoas Abdi Winoto; Firosalia Kristin; Indri Anugraheni (Universitas Negeri Medan, 2019)
Abstract: The purpose of this study is to 1) Describe the steps in applying PBL in increasing the activeness and thematic learning outcomes of class 4, 2) To find out the increase in activeness through the application of PBL in grade 4, 3) Class 4 the type of research is Classroom Action research (CAR). This study was conducted in 2 cycles using the Kemmis and Taggart model design consisting of 3 stages, namely planning, implementation and observation (acting and observing) and reflection (reflecting). The data collection instruments used were questionnaire sheets, observation sheets and written test. The subjects in this study were fourth grade student of Bringin 02 Elementary School Semarang Regency, amouting to 36 students. The results of this study indicate the percentage increase in student activity from the pre cycle which is categorized as student activity is very high and high only 16.66% to 41.67% in the first cycle and increased again in the second cycle to 77.78%. This increase also has a good impact on the percentage of student learning completeness, which initially only 36.11% of students completed increased to 58.33% in the first cycle and increased again in the second cycle to 86.11%. The result of the study with the problem based learning model prove that this model can improve the activity and learning outcomes pf 4th grade students at Bringin 02 Elementary School Semarang Regency in semester II of 2018/2019 Academic Year. Keyword : Problem Based Learning (PBL), Student Activity, Learning Outcomes Abstrak: Tujuan penelitian ini untuk 1) mendeskripsikan langkah-lengkah penerapan PBL dalam meningkatkan keaktifan dan hasil belajar tematik siswa kelas 4, 2) Untuk mengetahui peningkatan keaktifan melalui penerapan PBL pada siswa kelas 4, 3) Untuk mengetahui peningkatan hasil belajar tematik melalui penerapan PBL pada siswa kelas 4. Jenis penelitian yang dilakukan adalah Penelitian Tindakan Kelas (PTK).Penelitian ini dilakukan dalam 2 siklus dengan menggunakan desain model Kemmis dan Taggart yang terdiri dari 3 tahap yaitu perencanaan (planning), pelaksanaan dan pengamatan (acting and observasing) dan refleksi (reflecting). Instrumen pengumpulan data yang digunakan adalah lembar angket, lembar observasi dan tes tertulis. Subjek dalam penelitian ini yaitu siswa kelas 4 SDN Bringin 02 Kabupaten Semarang yang berjumlah 36 siswa. Hasil penelitian ini menunjukkan persentase peningkatan keaktifan siswa dari pra siklus yang dikategorikan keaktifan siswa sangat tinggi dan tinggi hanya 16.66% menjadi 41.67% pada siklus ke I dan meningkat lagi pada siklus ke II menjadi 77.78%. Peningkatan ini berdampak baik juga bagi persentase ketuntasan belajar siswa yang awalnya hanya 36.11% siswa yang tuntas, meningkat menjadi 58.33% pada siklus I dan meningkat lagi pada siklus II menjadi 86.11%. Hasil penelitian dengan model pembelajaran problem based learning ini membuktikan bahwa model ini dapat meningkatkan keaktifan dan hasil belajar siswa kelas 4 SDN Bringin 02 Kabupaten Semarang semester II Tahun Pelajaran 2018/2019. Kata Kunci : Problem Based Learning (PBL), Keaktifan Siswa, Hasil Belajar